Abnormal sweating patterns associated with itching, burning and tingling of the skin indicate possible underlying small‐fibre neuropathy. (18th January 2015) - Flores, S.; Davis, M.D.P.; Pittelkow, M.R.; Sandroni, P.; Weaver, A.L.; Fealey, R.D.
Summary Background Itching, burning, numbness and tingling of the skin are frequent reasons for dermatology consultation. We hypothesized that these sensations may be attributable to a small‐fibre neuropathy. Sweating, which is mediated by small nerve fibres, may be a surrogate marker of small‐fibre neuropathy. Objectives To investigate the results of thermoregulatory sweat testing (TST), which depicts and estimates whole‐body sweating, in patients with itching, burning, numbness and tingling sensations. Methods We retrospectively reviewed the medical records of 227 patients with itching, burning, numbness and tingling sensations involving the skin who were seen at our institution during 2008 and also underwent TST. Results The mean age of the cohort was 54 years (range 3–89), and 58% were female. In all, 149 patients (66%) had abnormal TST results; in 119 (80%) of these patients the areas of anhidrosis on TST corresponded to their symptomatic areas. For each symptom analysed separately, the area of anhidrosis correlated with the area of symptoms in most patients. Conclusions Patients with burning, itching, numbness and tingling have abnormal sweating patterns and often do not sweat in the symptomatic areas. These novel findings suggest that a small‐fibre neuropathy may underlie many cutaneous symptoms and that the neuropathy can be estimated using TST.